Global population trends in shorebirds: migratory behaviour makes species at risk - Koleček, Jaroslav; Reif, Jiří; Šálek, Miroslav; Hanzelka, Jan; Sottas, Camille; Kubelka, Vojtěch (Die Naturwissenschaften, 2021)
Linking population trends to species' traits is informative for the detection of the most important threatening factors and for assessing the effectiveness of conservation measures. Although some previous studies performed such an analysis at local to continental scales, the global-scale focus is the most relevant for conservation of the entire species. Here we evaluate information on global population trends of shorebirds, a widely distributed and ecologically diversified group, where some species connect different parts of the world by migration, while others are residents. Nowadays, shorebirds face rapid environmental changes caused by various human activities and climate change. Numerous signs of regional population declines have been recently reported in response to these threats. The aim of our study was to test whether breeding and non-breeding habitats, migratory behaviour (migrants vs. residents) and migration distance, breeding latitude, generation time and breeding range size mirror species' global population trends. We found that a majority of shorebird species have declined globally. After accounting for the influence of traits and species taxonomy, linear mixed-effects models showed that populations of migratory shorebirds decreased more than populations of residents. Besides that, declines were more frequent for species breeding at high latitudes of the Northern Hemisphere, but these patterns did not hold after excluding the non-migratory species. Our findings suggest that factors linked to migration, such as habitat loss as well as deterioration at stop-over or wintering sites and a pronounced climate change impact at high latitudes, are possible drivers of the observed worldwide population decreases.
Keywords: Behavior, Animal; Migration flyway; Climate Change; ekosystém; Conservation; Habitat deterioration; Waders; migrace zvířat; Life history strategy; Climate change; rozšíření zvířat; Birds; klimatické změny; zvířata; populační dynamika; chování zvířat; Animal Distribution; Population Dynamics; ptáci; Ecosystem; Animal Migration; Animals